97. Ilium chondromyxoid fibroma misdiagnosed as radiculopathy during pregnancy. Issue 1 (January 2015) - Stipa, G.; Luzzati, A.; Scotto, G.; Chiarini, P.; Floridi, P.
<x xml:space="preserve">Abstract</x> Chondromyxoid fibroma is a rare benign bone tumor, often misdiagnosed. A 39 years old woman, during first months of pregnancy, referred bilateral lumbar pain, with irradiation to the right leg, and painful paresthesias with radicular distribution (bilateral L5/S1). Symptomatology modified with a circadian rhythm, with a nocturnal exacerbation. Clinical examination documented: a positive right Lasegue sign, an absence of achilleum reflex, and tenderness at the sacroiliac articulation. Before pregnancy, patient presented recurrent episodes of radicular pain at right L5/S1 level. MRI showed hernia discal protrusions at the L4–L5 and L5–S1 levels, while electrophysiologic study exhibited a bilateral chronic radiculopathy L5–S1. After spontaneous miscarriage, patient underwent to another MRI, with extension to pelvis. This exam showed a multiloculated lytic lesion at right ilium level. A CT pointed out a cortical distruption, and extension to adjacent gluteal region. Bioptic material suggested a probable diagnosis of chondromyxoid fibroma, but only surgical excision and definitive histology confirmed this suspect. Ilium localization of this rare tumor made diagnosis difficult and often mistaken with other pathologies.